Corrigendum: Decreased expression of programmed death ligand-L1 by seven in absentia homolog 2 in cholangiocarcinoma enhances T-cell–mediated antitumor activity - Zheng, Hao; Zheng, Wen-juan; Wang, Zhen-guang; Tao, Yuan-ping; Huang, Zhi-ping; Yang, Le; Ouyang, Liu; Duan, Zhi-qing; Zhang, Yi-nuo; Chen, Bo-ning; Xiang, Dai-min; Jin, Gang; et al. (Frontiers in Immunology, 2022)
Corrigendum: Decreased Expression of Programmed Death Ligand-L1 by Seven in Absentia Homolog 2 in Cholangiocarcinoma Enhances T-Cell–Mediated Antitumor Activity